2017
DOI: 10.1007/s11419-017-0363-z
|View full text |Cite|
|
Sign up to set email alerts
|

Earwax as an alternative specimen for forensic analysis

Abstract: In this work, we presented, for the first time, earwax as an alternative forensic specimen for detecting 12 neuropsychotic drugs employing liquid chromatographytandem mass spectrometry in positive and negative ion modes after straightforward extraction with methanol. The method was validated and standard curves were established by external calibration with correlation coefficients [0.99. All precision, accuracy, matrix effects, extraction recoveries, and carryover were within acceptable limits; limits of quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…On the other hand, earwax was most recently used as a medium for monitoring drugs specially to indicate administration of drugs of abuse or drug facilitated crimes antiepileptics, anxiolytics, antipsychotics, etc. Cerumen could be even considered a more favourable surrogate to traditionally used biological fluids because of its non-invasiveness, ease of sample collection, minimum sample pretreatment, and relatively less external contamination in addition to being able to detect the analytes recently administered as well as drugs administered some months ago ( 78 ).…”
Section: Cerumen and Implications To Health Diagnostics And Forensicmentioning
confidence: 99%
“…On the other hand, earwax was most recently used as a medium for monitoring drugs specially to indicate administration of drugs of abuse or drug facilitated crimes antiepileptics, anxiolytics, antipsychotics, etc. Cerumen could be even considered a more favourable surrogate to traditionally used biological fluids because of its non-invasiveness, ease of sample collection, minimum sample pretreatment, and relatively less external contamination in addition to being able to detect the analytes recently administered as well as drugs administered some months ago ( 78 ).…”
Section: Cerumen and Implications To Health Diagnostics And Forensicmentioning
confidence: 99%
“…In humans, our recent studies demonstrated that cerumen could be used to diagnose types I and II diabetes mellitus (Shokry, de Oliveira, Avelino, de Deus, & Filho, 2017). In addition, cerumen can be used for tracking human exposure to tobacco (Shokry, de Oliveira, Avelino, de Deus, Pereira, et al, 2017), as an alternative biomatrix to forensic applications for drug abuse monitoring (Shokry, Marques, Ragazzo, Pereira, & Filho, 2017), and for cancer diagnosis (Barbosa et al, 2019). In animals, the volatile cerumen compounds have been used to detect the toxic principle in cattle intoxication by Palicourea marcgravii (Shokry, dos Santos, et al, 2017) and to assess disorders in sheep in peri‐parturition stage (Shokry, Pereira, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group successfully used cerumen VOMs to diagnose diabetes mellitus (DM) and differentiate between DM type I and II 29 . We have also investigated the viability of cerumen to diagnose intoxications and metabolic alterations in animals 25,30 , as well as for forensic applications as a monitoring biomatrix for drug abuse analysis 31 .…”
Section: Introductionmentioning
confidence: 99%